Evaluation of Spin in Abstracts of Systematic Reviews and Meta-analyses Focused on Treatments of Erectile Dysfunction: A Cross-sectional Analysis. Issue 1 (5th December 2020) - Reddy, Arjun K.; Lulkovich, Kaley; Ottwell, Ryan; Arthur, Wade; Bowers, Aaron; Al-Rifai, Shafiq; Cook, Katherine; Wright, Drew N.; Hartwell, Micah; Vassar, Matt
Abstract: Introduction: It is predicted that erectile dysfunction will affect around 322 million men worldwide by 2025. Because of the large volume of literature on the topic, physicians often turn to systematic reviews and meta-analyses—and particularly abstracts of such articles—for clinical guidance. Thus, it is crucial that findings are not misrepresented in abstracts. In this study, we evaluated the use of spin (ie, the misreporting of study findings by overstating or selectively reporting efficacy results, minimizing harms, or making unwarranted clinical recommendations) in the abstracts of systematic reviews on erectile dysfunction. Methods: A search strategy was developed using the MEDLINE and Embase databases to retrieve systematic reviews focused on treatments for erectile dysfunction. 2 investigators independently screened the titles and abstracts from the reviews for study inclusion. Investigators analyzed the included systematic reviews for 9 of the most severe types of spin using a previously developed classification scheme and rated them for methodological quality using the revised A MeaSurement Tool to Assess systematic Reviews (AMSTAR) in a masked, duplicate manner. Study characteristics for each review were also extracted in duplicate. Results: Our search returned 2, 224 articles, of which 102 systematic reviews and meta-analyses were included in the final analysis. A total of 31.4% (32/102) of systematic reviews contained spin. 8 types of spin were identified in our sample. Type 3 (selective reporting of or overemphasis on efficacy outcomes) and type 5 (conclusion claims beneficial effect despite high risk of bias) were the most common types of spin, each occurring in 10.8% (11/102) of abstracts. There was no significant association between the presence of spin and the extracted study characteristics or methodological quality. Conclusion: Spin was present in systematic reviews and meta-analyses covering erectile dysfunction treatments. Steps should be taken to improve the reporting quality of abstracts on erectile dysfunction treatment.